PENGARUH USIA TERHADAP REGULASI DIRI AKADEMIK MAHASISWA PADA KONDISI STUDY FROM HOME - Eka Apristian Pantu (Psibernetika, 2021)
The increasingly massive Covid-19 transmission forces universities to carry out study from home (SFH) activities. In SFH, individuals are required to organize their own learning at home, so the learning can run effectively. The ability of individuals to regulate their own learning is called self-regulated learning (SRL). Age is one of the factors that can influence SRL. The study was conducted to examine the effect of age on SRL. Respondents in this study were 296 students from all over Indonesia who were selected through the incidental sampling method. This study uses a self regulated learning scale that has been adapted into Indonesian. The results showed that age had a significant and positive effect on individual SRL (p= 0,008, β=0,153).